THE EFFECTIVENESS OF USING ENGLISH SONGS ON SPOTIFY FOR ENHANCING LISTENING SKILL IN EIGHTH-GRADE STUDENTS AT MTS N 1 JEPARA IN THE ACADEMIC YEAR 2023/2024 - Risyadatun Ni'mah; Aprilia Riyana Putri (PROJECT (Professional Journal of English Education), 2024)
This research aims to determine the significant difference between students’ listening skill before and after being instructed using English songs. The eighth-grade students at MTs N 1 Jepara were still struggling with their vocabulary and listening skill. In order to enhance students' listening skill, the researcher utilized English songs from Spotify. A true-experimental scheming with a pretest-posttest control group pattern was used in this study. The total population of the study was 376 students who taken randomly to be sampled. Pre-test and post-test of the experimental class scores were higher than those of the control class. This demonstrated that the experimental class's scores were prominent diverse before and after the use of Spotify media as a treatment. The pre-test and post-test scores in the Mann-Whitney test had Asymp. Sig. (2-tailed) values of 0.000<0.05 and 0.001<0.05. That indicates that Ho was turned down and Ha was approved. Thus, it might be assumed that English songs on Spotify were effective for enhancing students’ listening skill of MTs N 1 Jepara.